2020
DOI: 10.1177/1077800420938879
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Dialogic Literary Gatherings on Students’ Relationships With a Communicative Approach

Abstract: Taking a communicative approach in a qualitative inquiry entails including people’s voices through dialogues that are egalitarian and oriented toward transformation. This approach aligns with the transformative paradigm in the pursuit of ensuring the inclusion of the most vulnerable groups. This article explores the role of the communicative approach when conducting a case study in an elementary school to study the impact of dialogic literary gatherings (DLGs) on students’ relationships, particularly for those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
4
20
0
6
Order By: Relevance
“…This article discusses the impact of participating in two educational activities previously defined as successful educational actions (SEAs) [ 7 ] on attitudes towards learning shown by students who have participated in these actions. Thus far, we have clear evidence of the positive impact that SEAs have on learning outcomes [ 11 – 15 ], and there are studies suggesting that there is also a positive effect on the coexistence and cohesion of the group-class [ 16 , 17 ]. However, previous studies have not explored the impact that such SEAs may have on students’ own attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…This article discusses the impact of participating in two educational activities previously defined as successful educational actions (SEAs) [ 7 ] on attitudes towards learning shown by students who have participated in these actions. Thus far, we have clear evidence of the positive impact that SEAs have on learning outcomes [ 11 – 15 ], and there are studies suggesting that there is also a positive effect on the coexistence and cohesion of the group-class [ 16 , 17 ]. However, previous studies have not explored the impact that such SEAs may have on students’ own attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The decision-making process for the implementation of the online DLG during the lockdown is based on existing evidence that this intervention is a successful educational action that improves cognitive, social and emotional well-being (33,35,36,64). However, this process of decision-making and implementation goes beyond the EIDM and responds to the so-called dialogic recreation of knowledge (DRK) (16,32,37).…”
Section: Resultsmentioning
confidence: 99%
“…The interviews collect the postulates of the communicative methodology of research ( 15 , 36 , 48 ). The interviews using a communicative approach are conducted as open conversations in which the researcher shares the existing evidence with the interviewee.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When implemented in regular schools, students with SEN participate in the DLGs in an equal way, minimizing the differences between them and the rest of the students (Molina Roldán, 2015). Research (García-Carrión et al, 2020) has indicated that, through the DLGs, the low expectations and prejudices some students with disabilities have to face can be transformed. In this regard, DLGs have shown not only to contribute to the integration of students with SEN to their class but also to foster their instrumental learning (Molina Roldán, 2015).…”
Section: Dialogic Literary Gatherings and Students With Senmentioning
confidence: 99%